Utilização de um algoritmo de caminho mínimo no processo de recolhimento do palhiço da cana-de-açúcar - Silva, Inara Soldera Romano da [UNESP] (2011)
The current concern with environment has made sugarcane producers invest in changes in harvest system. The changes consist in reducing the burning of the crops prior to harvest and use mechanized cutting. Mechanized harvesting produces large amount of waste in the ground (leaves, straw and fractions of the stem), creating favorable conditions for the emergence of parasites and damaging the new bud, delaying the next harvest. Several authors have shown the feasibility of using crop residue for energy production, but the great difficulties found in using this residue for power generation is the large number of machinery involved in the collection system of this waste and the high cost of this process, especially transport cost. Among the many options for collection of crop residue from the field, one has been much discussed and used: the removal of crop residue in bales. The aim of this study is apply mathematical optimization techniques to collect the bales of crop residue in the plots, mapped by techniques of Precision Agriculture. We use a variation of Dijkstra's algorithm to determine the shortest path route. The technique adopted for collecting the bales showed to be adequate.